TODAY’S CONSUMERS ON THE MARKET IN CSÍKSZEREDA (MIERCUREA CIUC) - Péter, Emőke Katalin; Illyés, László (Applied Studies in Agribusiness and Commerce, 2024)
Due to the geographical situation of Harghita County, farming mostly in small agricultural areas encourages farmers to engage in more integrated agricultural activities. As a result, more and more farmers who are open to development are starting to appear on local markets with processed products. The traditional knowledge passed down from generation to generation on small local farms is similar in families living in each area and therefore socially reinforcing. Older farmers in our countryside have mostly shied away from the new knowledge of the mega-manager, but their younger, more highly skilled counterparts are more willing to open up to new knowledge. The demand for local products with a historical basis has been gradually increasing in recent years. To save costs, they also sell their products at the market themselves. In order to meet today’s consumer needs, in addition to the production, processing and packaging of raw materials, producers must also think about branding, logistics and design. Customer relations and quality communication are essential for a well-functioning business (PG Balogh et.al, 2021) In Harghita County, farmers running a traditional small-scale farm mostly face marketing problems. At the same time, the demand for high quality products produced in a sustainable way is increasing. The aim of our empirical study is to investigate the expectations of consumers visiting the Traditional Products Fair in Csíkszereda (Miercurea -Ciuc) using artificial intelligence methods. These habits have their origins in the market habits of the past centuries, therefore, our research tries to reveal the atmosphere of the markets of the past.